Erectile Dysfunction and Premature Ejaculation: Interrelationships and Psychosexual Factors. (1st February 2015) - Brody, Stuart; Weiss, Petr
Abstract: Introduction: Both erectile dysfunction (ED) and premature ejaculation (PE) impair the quality of sexual intercourse for both men and their female partners. Aims: This study aims to examine with a large representative sample the interrelationships of measures of ED, PE, typical intravaginal ejaculatory latency time (IELT), men's perceived relationship quality with their mother, and age of first being in love. Methods: In this cross‐sectional study, a nationally representative sample of 960 Czech coitally experienced men (aged 15–84), provided age, International Index of Erectile Function 5‐item (IIEF‐5), Index of Premature Ejaculation (IPE) scores, IELT, rating of relationship with their mother, and age at first being in love. Main Outcome Measures: Correlations, partial correlations adjusting for age, analysis of covariance (ANCOVA), and multiple regression statistical methods were used. Results: IIEF‐5, IPE, and IELT were significantly intercorrelated (IIEF‐5 and IPE: r = 0.64). Better IIEF‐5 scores were associated with younger age at first (and ever) being in love. Poorer IPE score, shorter IELT, and mild–moderate ED were associated with poorer perceived mother relationship (which was also associated with first being in love at an older age). Multiple regression analyses revealed that: (i) greater IELT was associated with better erectile function and better mother relationship, but not with age; and (ii) IELT of <1 minute was associated with poorer perceived mother relationship and poorer IIEF‐5, but marginally with age. History of homosexual activity was unrelated to IIEF‐5, IPE, IELT, and perceived mother relationship scores. Conclusions: The findings suggest that degrees of ED and PE are often comorbid, and both ED and PE are associated with less favorable early experiences with women.